2002
DOI: 10.2337/diabetes.51.6.1957
|View full text |Cite
|
Sign up to set email alerts
|

Thrombomodulin Deficiency in Human Diabetic Nerve Microvasculature

Abstract: Human diabetic neuropathy is multifactorial in etiology, with ischemia as a final common pathology. Although impaired vascular endothelial cell function in diabetic microvascular injury is established, the role of thrombomodulin (TM)-dependent protein C antithrombotic mechanism in the pathogenesis of neuropathy is unclear. This neuropathologic case-control study investigated whether vascular endothelial TM expression is deficient in peripheral nerve microvessels in diabetic neuropathy. Sural nerve biopsies fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
1
2

Year Published

2002
2002
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 37 publications
1
16
1
2
Order By: Relevance
“…58 It has been reported that plasma thrombomodulin from the endothelium caused by reduction of APC are increased in diabetic patients, and the impairment of the thrombomodulin/protein C system is associated with DN. 59 Isermann et al 60 recently reported that APC may delay the onset of nephropathy in long-term experimental diabetes by modulating apoptosis of endothelial cells and podocytes.…”
Section: Neutralizing Agents Against Hyperglycemia’s Toxic Metabolitesmentioning
confidence: 99%
“…58 It has been reported that plasma thrombomodulin from the endothelium caused by reduction of APC are increased in diabetic patients, and the impairment of the thrombomodulin/protein C system is associated with DN. 59 Isermann et al 60 recently reported that APC may delay the onset of nephropathy in long-term experimental diabetes by modulating apoptosis of endothelial cells and podocytes.…”
Section: Neutralizing Agents Against Hyperglycemia’s Toxic Metabolitesmentioning
confidence: 99%
“…Alternatively, NF-κB activation in cells of the vessel wall of the vasa nervorum could lead to vascular dysfunction, and, subsequently, to neuronal dysfunction. An association between microangiopathy and neuropathy has long been considered (2,6,10,45), and the AGE-RAGE axis could be one mechanism by which vascular changes ultimately lead to neuronal damage. This interpretation is supported by the observation that the colocalization of CML, RAGE, NF-κB, and IL-6 was restricted to epineurial vessels, perineurium, and endoneurial vessels (Figure 1), while axons from both patients with diabetes and nondiabetic controls were negative for each of the 4 antigens.…”
Section: Figurementioning
confidence: 99%
“…In particular, augmented synthesis of factor VII, thrombin, tissue factor and PAI-1 is detected in the diabetic patient, while anticoagulative substances, such as thrombomodulin and protein C, are diminished [10][11][12].…”
Section: Introductionmentioning
confidence: 99%